2019
DOI: 10.1039/c8fd00179k
|View full text |Cite
|
Sign up to set email alerts
|

Light induced formation of a surface heterojunction in photocharged CuWO4 photoanodes

Abstract: Photocharging of CuWO4 photoanodes enhances its water oxidation kinetics as a result of improved charge separation near the electrode/electrolyte interface post photocharging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…BiVO 4 was used as a model multinary photoanode in this study; however, similar PEC performance enhancements from photocharging have been reported for other multinary metal oxides such as CuWO 4 and Fe 2 TiO 5 and in heavily doped metal oxide photoelectrodes, suggesting that this might be a very common phenomenon in different multinary metal oxide photoelectrodes. The time scale of this dissolution (minutes to hours) implies that this effect is very relevant to a lot of lab-scale studies and fundamental research performed on these materials and, as such, should be accounted for.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…BiVO 4 was used as a model multinary photoanode in this study; however, similar PEC performance enhancements from photocharging have been reported for other multinary metal oxides such as CuWO 4 and Fe 2 TiO 5 and in heavily doped metal oxide photoelectrodes, suggesting that this might be a very common phenomenon in different multinary metal oxide photoelectrodes. The time scale of this dissolution (minutes to hours) implies that this effect is very relevant to a lot of lab-scale studies and fundamental research performed on these materials and, as such, should be accounted for.…”
Section: Discussionsupporting
confidence: 54%
“…20−23 The time scale of this effect was shown to be on the order of minutes to hours. 20−23 Until now, similar enhancements from photocharging have been demonstrated for BiVO 4 , 20−23 CuWO 4 , 24 Fe 2 TiO 5 , 25 and Bi 4 TaO 8 X 26 and in heavily doped binary metal oxide photoanodes, 27,28 indicating that this could be a common phenomenon in multinary metal oxide photoelectrodes. Hence, BiVO 4 is chosen in this work as a model multinary metal oxide photoelectrode, and as such, the findings here can be extended to other commonly used multinary metal oxide photoelectrodes.…”
Section: ■ Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…In most cases, the understanding of photocatalysis could be realized by characterizing photocatalysts before and after photocatalytic reactions, providing an experimental basis to deduce the photocatalytic process. Nevertheless, because high-energy electrons and holes generated from semiconductor photocatalysts upon light irradiation play roles as “reactants” in photocatalytic reactions, which not only participate in the surface catalytic reactions at the outer surface but also involve the possible reconstruction or self-activation of photocatalysts before the photogenerated charges reach the outer surface, making the photocatalytic mechanism elusive. Various in situ characterization techniques have been applied for widely exploring the in situ surface activation in electrolysis and interactions between photogenerated charges and semiconductors as well as the cocatalysts in photoelectrocatalysis, indicating abundant and sophisticated transformation processes at interfacial regions. Photoinduced absorption and electrochemical techniques were used to investigate the charge carrier dynamics of photoelectrochemical water oxidation on BiVO 4 both with and without cobalt phosphate cocatalyst . X-ray absorption fine structure (XAFS) spectroscopy was used to analyze the photoexcited hole transfer to a MnO x cocatalyst on a SrTiO 3 photoelectrode .…”
mentioning
confidence: 99%
“…In the 3 rd Faraday Discussion on Artificial Photosynthesis in Cambridge, UK, different possible approaches to develop a functional and commercially viable solar-to-chemical energy conversion device were covered ( Figure 1). These approaches are based on different classifications of Artificial Photosynthesis research, which depend on the nature of the materials used (Section 2.1), [32][33][34][35][36][37][38][39][40][41][42][43][44][45] the degree of system integration (Section 2.2), [46][47][48][49] and the substrates and products involved (Section 2.3). [50][51][52][53] In this article, we will firstly discuss the main motivations for Artificial Photosynthesis research.…”
Section: Introductionmentioning
confidence: 99%